Analisis Kemampuan Literasi Sains Ditinjau dari Aspek Kompetensi Sains Siswa pada Materi Global Warming - Musa, Weny J.A; Zainudin, Farnawaty; Isa, Ishak; Kilo, Jafar La; Kilo, Ahmad Kadir (Universitas Negeri Gorontalo, 2023)
The context of global warming material also takes into account aspects of scientific competence. Data was collected through a multiple choice test consisting of 12 questions. The results of the research show that: (1) The majority of students' scientific literacy abilities in class VIII of SMP Negeri 1 Gorontalo as a whole in the aspect of science competency are relatively low, with a student percentage of 91.16%. Apart from that, scientific literacy skills in competency aspects, such as explaining phenomena scientifically (34.35%), evaluating and designing scientific inquiries (42%), and interpreting data & evidence scientifically (28.23%), are also relatively low. (2) The majority of students' scientific literacy abilities in class VIII of SMP Negeri 2 Gorontalo as a whole in the scientific competency aspect are also relatively low, with a student percentage of 95.68%. Likewise, scientific literacy abilities in competency aspects, such as explaining phenomena scientifically (33.95%), evaluating and designing scientific inquiries (30.25%), and interpreting data & evidence scientifically (30.71%), are also classified as low